Migration, Ethnicity and Progression from Low-Paid Work: Implications for Skills Policy. Issue 4 (13th November 2014) - Netto, Gina; Hudson, Maria; Noon, Mike; Sosenko, Filip; de Lima, Philomena; Kamenou-Aigbekaen, Nicolina
<x content-type="archive" xml:space="preserve">Abstract</x> Migration plays an important role in determining skills supply, and certain ethnic groups tend to be over-represented in low-paid work. This article considers the implications of the complex interplay of migration, ethnicity and workplace progression for skills policy by comparing and contrasting the opportunities faced by low-paid workers of diverse ethnicities in progressing to better paid work. This is done by drawing on a qualitative study of nine case study organisations in Scotland and England, including interviews with sixty-five workers and forty-three managers. We argue that while all low-paid workers face formidable barriers to progression, recent migrants and settled ethnic minorities face additional challenges that should be considered in skills and wider social policies related to low-paid work.